Plasticizing effect of coconut oil on morphological, mechanical, thermal, rheological, barrier, and optical properties of poly(lactic acid): A promising candidate for food packaging. Issue 41 (23rd June 2017) - Bhasney, Siddharth Mohan; Patwa, Rahul; Kumar, Amit; Katiyar, Vimal
ABSTRACT: This study explores the plasticizing effect of coconut oil (CO) on PLA for evaluating its suitability for flexible packaging. Changes in morphological, mechanical, thermal, rheological, barrier and optical properties of melt compounded Poly(lactic acid)–Coconut oil (PLA–CO) blend were investigated by varying the mixing ratio. Water vapor permeability of blends decreased by 58% at 7 wt % plasticizer content. The tensile strength showed a decreasing trend with increasing plasticizer percentage while the % elongation showed an increasing trend. At 7 wt % plasticizer content tensile strength decreased from 60 to 41 MPa and % elongation increased from 12% to 54%. Molecular weight ( Mn ) and onset of degradation ( T onset ), upon 1 wt % plasticizer addition showed a reduction of 6% and 0.6%, respectively, which were well within permissible limits required for polymer processing. The melt flow properties of the blends were slightly improved (∼16%) upon 5 wt % addition of CO. Transparency of the PLA films was improved by addition of plasticizer. FTIR spectra of PLA‐CO sample confirmed the interaction between PLA and coconut oil via hydrogen bonding. At higher loading, coconut oil shows very limited compatibility with PLA. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45390. Abstract :